Protease‐activated receptor antagonists prevent thrombosis when dual antiplatelet therapy is insufficient in an occlusive thrombosis microfluidic model - Jess Berry (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background Platelet activation and arterial thrombosis on a ruptured atherosclerotic plaque is a major cause of myocardial infarction. Dual antiplatelet therapy (DAPT), the combination of platelet aggregation inhibitors, aspirin and a P2Y12 antagonist, is used to prevent arterial thrombosis. However, many people continue to have arterial thrombosis and myocardial infarction despite DAPT, indicating that additional therapies are required where DAPT is insufficient. Objectives To determine whether antagonists of protease‐activated receptors (PARs) can prevent occlusive thrombosis under conditions where DAPT is insufficient. Methods We used human whole blood in a microfluidic model of occlusive thrombosis to compare conditions under which DAPT is effective to those under which DAPT was not. Cangrelor (a P2Y12 antagonist) and aspirin were used to mimic DAPT. We then investigated whether the PAR1 antagonist vorapaxar or the PAR4 antagonist BMS 986120, alone or in combination with DAPT, prevented occlusive thrombosis. Results and Conclusions A ruptured plaque exposes collagen fibers and is often rich in tissue factor, triggering activation of platelets and coagulation. Occlusive thrombi formed on type I collagen in the presence or absence of tissue factor (TF). However, although DAPT prevented occlusive thrombosis in the absence of TF, DAPT had little effect when TF was also present. Under these conditions, PAR antagonism was also ineffective. However, occlusive thrombosis was prevented by combining DAPT with PAR antagonism. These data demonstrate that PAR antagonists may be a useful addition to DAPT in some patients and further demonstrate the utility of in vitro models of occlusive thrombosis.